Pengaruh Kepuasan Kerja Terhadap Kinerja Perawat Rawat Inap Di RS X Medan - Husna, Fildza Rizki (Jurnal Kajian Kesehatan Masyarakat, 2024)
Improving the performance of inpatient nurses is crucial in the healthcare industry. Good nursing performance can have a positive impact on patient satisfaction and hospital reputation. As a result, it is critical that hospital administration addresses variables that may affect nurse performance and satisfaction. A welcoming and comfortable work atmosphere is one of the elements that might affect nurses' job happiness. The purpose of this study was to ascertain how the performance of inpatient nurses at X Medan Hospital was impacted by their level of work satisfaction. Researchers concentrated on variables that affect nurse performance, such as pay, relationships, advancement, and supervision. A survey with a randomly selected sample of thirty-six respondents was the study technique employed. Multiple linear regression analysis was used for the data analysis. The study's findings demonstrate the association between job satisfaction and nurse performance in the inpatient room at RS X Medan as well as salary, promotion, and supervision. This indicates that hospital management needs to address these factors for enhancing satisfaction and nursing performance, thereby providing better healthcare services to patients.